Incidence of acute aortic dissections : a systematic review and meta-analysis of population-based studies - Mourão, Mariana Oliveira (2022)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2021